1992
DOI: 10.3109/02656739209038005
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the expression of heat shock proteins by step-down heating and hypothermia in rat hepatoma cells with a different degree of heat sensitivity

Abstract: Thermosensitization induced by pretreatment at supra- and subnormal temperatures, rate of protein synthesis and expression of the major heat shock proteins under such conditions was investigated in relation to intrinsic heat sensitivity of rat hepatoma cells, i.e. Reuber H35 and HTC. The high degree of heat susceptibility of H35 cells was reflected by a high degree of thermosensitization after pretreatment by heat (step-down heating) at temperatures of 42-44 degrees C for 30 min or cold for 16 h at temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…To study the effect of homologous heat postconditioning, cells were first exposed to a heat shock at 42°C or 43.5°C and subsequently incubated at mild 'fever-like' temperatures. An enhanced survival capacity and an enhanced synthesis of stress proteins were observed when the initial heat shock was followed by a post-exposure to a lower hyperthermic (fever-like) temperature (Schamhart et al 1992;Van Wijk et al 1994a). Similar observations were reported by Delpino et al (1992).…”
Section: Homologous Postconditioning Hormesissupporting
confidence: 82%
“…To study the effect of homologous heat postconditioning, cells were first exposed to a heat shock at 42°C or 43.5°C and subsequently incubated at mild 'fever-like' temperatures. An enhanced survival capacity and an enhanced synthesis of stress proteins were observed when the initial heat shock was followed by a post-exposure to a lower hyperthermic (fever-like) temperature (Schamhart et al 1992;Van Wijk et al 1994a). Similar observations were reported by Delpino et al (1992).…”
Section: Homologous Postconditioning Hormesissupporting
confidence: 82%
“…They were not induced at 41 C and only to a small degree after the HS at 42 C. However, the combination (42 C followed by 41 C) caused a significant induction. 19 Similar observations were reported for mRNA levels of hsp68 and hsp84 when heat-shocked cells were post-exposed to 40 C and 41 C. 23 These observations were supported by the work of Delpino et al 24 who demonstrated enhanced synthesis of stress proteins and enhanced survival capacity due to step-down heating.…”
Section: Results Of Homologous Studies (Isopathic Approach)supporting
confidence: 55%
“…Schamhart et al 19 exposed cells initially for 30 min at either 42 C or 43.5 C and subsequently incubated them at mild (fever-like) temperatures (38-41 C) for 6 h. The survival capacity was then tested by exposing cells to a test treatment of 43.5 C for 1 h. 19,23 When cells were initially heat shocked at 42 C, a posttreatment of 40 C enhanced the survival capacity compared to cells that were exposed to 42 C and post-treated at 37 C. With this mild postconditioning, heat treatment appeared to be beneficial following the 42 C heat treatment, but it depressed the survival capacity of cells that had been exposed to 43.5 C pretreatment. Interestingly, the exposure of untreated cells to 40 C for 6 h was without effect on survival capacity.…”
Section: Results Of Homologous Studies (Isopathic Approach)mentioning
confidence: 99%
See 2 more Smart Citations